Articuler les dimensions constitutives de l’éducation aux médias - Normand LANDRY (Tic & Société)
This article provides a critical review of the English-language literature on media education. It presents its constitutive dimensions and particularities; it further characterizes media education as a recent and distinct field growing rapidly. This field brings together theoretical knowledge, pedagogical practices, sought-after competencies and policies. These elements are introduced and described. This article also proposes three criticisms of scholarly writings. Firstly, they show a high level conceptual confusion concerning the sets of knowledge and competencies that media education tries to foster. They also struggle to articulate the constitutive dimensions of the field with relation to one another. Finally, the analysis of public policies, particularly of school curricula, is peripheral and incomplete. Knowledge of curriculum content and school-based practices remains underdeveloped.